2014
DOI: 10.1039/c4cc00811a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a crown ether-like supramolecular library by conjugation of genetically-encoded peptide linkers displayed on bacteriophage T7

Abstract: By using the 10BASEd-T, we have synthesized a crown ether-like macrocyclic library possessing randomized peptide linkers on bacteriophage T7. Among 1.5 × 10(9) diversities of the supramolecule candidates, we have obtained a specific binder for the N-terminal domain of Hsp90.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Alternative small-molecule scaffolds, such as 1,3,5-triacryloyl-1,3,5-triazinane, N,N’,N’’ -(benzene-1,3,5-triyl)tris(2-bromoacetamide), and N,N’,N’’ -benzene-1,3,5-triyltrisprop-2-enamide have been employed to generate bicyclic peptides with different core structures (i.e., flexibility and size) [39,40]. Phage display libraries containing crown ether-like macrocycles (constructed with N,N’ -[1,2-ethanediyl-oxy-2,1-ethanediyl]bis(2-bromoacetamide)) and photo-switchable azobenzene linkers (e.g., 3,3’-bis(sulfonato)-4,4’-bis(chloroacetamido)-azobenzene have also been developed by the Heinis and Derda groups, respectively [41,42].…”
Section: Methods For Discovery Of Macrocyclic Ppi Inhibitorsmentioning
confidence: 99%
“…Alternative small-molecule scaffolds, such as 1,3,5-triacryloyl-1,3,5-triazinane, N,N’,N’’ -(benzene-1,3,5-triyl)tris(2-bromoacetamide), and N,N’,N’’ -benzene-1,3,5-triyltrisprop-2-enamide have been employed to generate bicyclic peptides with different core structures (i.e., flexibility and size) [39,40]. Phage display libraries containing crown ether-like macrocycles (constructed with N,N’ -[1,2-ethanediyl-oxy-2,1-ethanediyl]bis(2-bromoacetamide)) and photo-switchable azobenzene linkers (e.g., 3,3’-bis(sulfonato)-4,4’-bis(chloroacetamido)-azobenzene have also been developed by the Heinis and Derda groups, respectively [41,42].…”
Section: Methods For Discovery Of Macrocyclic Ppi Inhibitorsmentioning
confidence: 99%
“…13,14 This gp 10 based-t hioetherificaion (10BASE d -T) is carried out in a one-pot reaction without side reactions or loss of phage infectivity. Consequently, the cores can coevolve during selection for target specific binders with the phage display technology.…”
mentioning
confidence: 99%
“…These results suggested that both structures of the fluorogenic core and the rest of the surrounding peptide were essential for the GST-specific binding. Thermodynamic parameters were also obtained from ITC, 14 and favorable enthalpy and entropy changes (Δ H and Δ S ) were observed. These suggest that hydrogen bonding and van der Waals force, as well as hydrophobic effect, moderately contributed to the interaction between the Prodan-evolver 1 and GST.…”
mentioning
confidence: 99%
“…Macrocyclic peptides are an attractive class of potential pharmaceutical agents able to interact with a variety of protein targets . Ribosomal construction and selection‐based screening of peptide libraries has proven to be a promising strategy to identify cyclic peptide ligands with high affinity to designated targets Although there are various methodologies reported to date, the combination of mRNA display method with genetic code reprogramming, which we refer to as the RaPID (Random nonstandard Peptides Integrated Discovery) system, has enabled us to rapidly discover de novo macrocyclic peptide ligands from vast libraries (over 10 12 molecules) against protein targets of interest . In particular, its versatility for encoding diverse exotic building blocks ( e. g .…”
Section: Figurementioning
confidence: 99%
“…Macrocyclic peptides are an attractive class of potential pharmaceutical agents able to interact with a variety of protein targets. [1][2][3][4][5] Ribosomal construction and selection-based screening of peptide libraries has proven to be a promising strategy to identify cyclic peptide ligands with high affinity to designated targets [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Although there are various methodologies reported to date, the combination of mRNA display method [21][22] with genetic code reprogramming, which we refer to as the RaPID (Random nonstandard Peptides Integrated Discovery) system, has enabled us to rapidly discover de novo macrocyclic peptide ligands from vast libraries (over 10 12 molecules) against protein targets of interest. [23][24][25] In particular, its versatility for encoding diverse exotic building blocks (e. g. d-, [13] N-methylated, [13] carborane-containing amino acids, [26] and even non-amino acids [27] ), and various macrocyclization modes (e. g., N-terminus-to-sidechain, [28] sidechain-to-sidechain, [29][30] and N-terminus-to-C-terminus [31][32] ) is extraordinarily useful for the discovery of a wide range of macrocycles.…”
mentioning
confidence: 99%